Guide :

help me to solve this problem.

Given that y varies jointly with x and with the square root of z, and that y=2 when x=1/8 and z=1/4 find i.a formula giving y in terms of x and z, and ii. the value of y when whn x=3/8 and z=1/9.

Research, Knowledge and Information :

Mathway | Math Problem Solver

Help. Sign In. Sign Up ... There was a problem saving your suggestion. ... To login with Facebook, you must allow Mathway to access your email address. Sign In:
Read More At :

Cymath | Math Problem Solver with Steps | Math Solving App

Solve calculus and algebra problems online with Cymath math problem solver with steps to show your work. Get the Cymath math solving app on your smartphone! Premium ...
Read More At :

WebMath - Solve Your Math Problem

WebMath is designed to help you solve your math problems. ... Are you stuck on a math problem? We'd like to help you solve it. Click on one of the tabs above.
Read More At :

Please help me to solve this problem? -

... (WGA) is here to help protect ... i was prepring to install wmp11 the adress come that my window copy is not geniune please help me to solve this problem.
Read More At :

SOLUTION: Please help me to solve this problem. A certain ...

Question 1054224: Please help me to solve this problem. A certain paint mixture weighing 305 kg contains 22% solids suspended in water.
Read More At :

, help me to solve this problem | Physics Forums - The Fusion ...

plz, help me to solve this problem ... Please help me to solve these problems (Replies: 2) Please help me solve this physic problem (Replies: 6)
Read More At :

Online Math Problem Solver -

Math Forum/Help; Problem Solver; Practice; Algebra; ... Online Math Problem Solver. ... You can solve all problems from the basic math section plus solving simple ...
Read More At :

Please help me to solve this problem -

Please help me to solve this problem Download png. 2. Ask for details ; Follow; Report; ... Somebody please help me! (Look at the bottom problem not the top) Mathematics;
Read More At :

Help Me To Solve This Problem - ENGLISH FORUMS

Help Me To Solve This Problem. Forums Topic of the Moment 1; ... Kashmir Problem; Help Me. Pls Help Me Out Of This Complicate GRAMMER; Help Me To Write Vacation Letter;
Read More At :

Help me to solve this problem Run-time error-2147418105 ...

Sep 16, 2008 · Experts Exchange > Questions > Help me to solve this problem Run-time ... Help me to solve this problem Run-time error-2147418105 (80010007)Automation erro ...
Read More At :

Suggested Questions And Answer :

how can you get the answer 7 while only using the number 2,0,1, and 2?

My there brethren and standing hear today, it just because what DR. UWA has done me for me with problem of my husband. Contact him at: [email protected]. I am using this opportunity to share the testimony of what DR. UWA has done, he help me in such away that I didn’t no now to thank him. Been through **** and pain, looking for a good and real spell caster who can help me get my husband back. I have been scammed my many spell cater, by some who claimed to be real spell casters. Until I found the real and great spell caster is name is Dr.UWA who helped me, and solved all my problems concerning my husband who left me since 3 years ago. and after that i also took my friend along, who was also having the same problem who help me to bring my husband, who left her since 2 year ago he help me with out no payment DR.UWA is a great doctor, whenever you are in any problem relationship please contact him at [email protected] It took me a very long period of time, before I could get this real and great spell caster. So right now is here, and the best for you to solve your problems please contact [email protected]
Read More: ...

How do you solve this problem? solve for d: n= m+3d/4

Problem: How do you solve this problem? solve for d: n= m+3d/4 I need help solving this and seeing how it was solved since I am having trouble figuring out what to do and how to solve it thanks. n = m + 3d/4 n - m = (m + 3d/4) - m n - m = 3d/4 4(n - m) = (3d/4)4 4(n - m) = 3d 4(n - m)/3 = 3d/3 4/3 (n - m) = d Answer: d = 4/3 (n - m)  
Read More: ...

Y=-3x+6 x+y=8

Problem: Y=-3x+6 x+y=8 I need help solving this problem with elimination.. y = -3x + 6 3x + y = 6 x + y = 8 Eliminate y by subtracting the second equation from the first (re-written) equation...  3x + y = 6 -(x + y = 8) --------------  2x      = -2 2x = -2 x = -1 Now, solve for y. y = -3x + 6 y = -3(-1) + 6 y = 3 + 6 y = 9 Check by using the second equation. x + y = 8 -1 + 9 = 8 8 = 8 Answer: x = -1, y = 9  
Read More: ...

6x+(5x-8) i need help to solve this problem

?????????????? "solv" ???????????????? problem ?????????????? yu dont hav equashun...gotta hav "=" tu hav a problem 6x+5x-8=0 11x=8 x=8/11=0.72727272727272727272...
Read More: ...

How do I solve mixture problems like this? 18+.3 (50-x)=.27(50)

Use BODMAS rule where start by opening brackets if your qstn involves brackets and then multiplication then addition then subtruction the ans you'll get will be the best ans ever. Multiply 3 by 50 u will get 150 then mltpy 3 by -x u will get -3x then your eqn will bee as follows 18+150-3x 27(50) then multply 27 and 50 it will be 1350then continue as i told in the begining with BODMAS rule where BO means brackets open ,Dmeans division ,M means multiplication ,A means addition and S means subtruction.this is the best way of solving it thank you.
Read More: ...

how do I solve x/3 + 6 =3? Please give me the steps.

how do I solve x/3 + 6 =3? Please give me the steps. Please help me with this math problem. I'm not sure how of the steps to solving it. Thank you. x/3 + 6 = 3 x/3 + 6 - 6 = 3 - 6 x/3 = -3 x/3 * 3 = -3 * 3 x = -9  
Read More: ...

Please help to solve for K: D=3K/K-8P. Desperate for help!

me assume that stuf shood be . . . d=3k/ (k-8p) . . . d(k-8p)=3k . . . dk -8pd -3k=0 . . k(d-3)-8pd=0 . . . k(d-3)=8pd . . . k=8pd/(d-3)
Read More: ...

x+3=-6, 12+x=-7, t+1/2=3/4

I'd be happy to help you out with this. :) Alright so when you are dealing with equations such as the one you have here: x + 3 = -6 You want to solve for the variable, in this case x.  In order to do that you need to get the variable by itself.  So what I would do is subtract the 3 from both sides. x + 3 = -6     -3     -3 ------------- x = -9 For the second problem: 12 + x = -7 You do the same thing, get the variable, x, by itself.  To do this subtract 12 from both sides. 12 + x = -7 -12        -12 --------------- x = -19 For the third problem: t + 1/2 = 3/4 you are dealing with fractions, but the idea is the same.  Get the variable by itself by subtracting 1/2 from both sides: t + 1/2 = 3/4     -1/2   -1/2 ---------------- t = 3/4 - 1/2 Now you want to combine like terms but in order to add or subtract fractions you must first get a common denominator. In this case the common denominator would be 4 so the only fraction that you have to change is the 1/2. Multiply 1/2 by 2/2 1/2 * 2/2 = 2/4 The new equation is: t = 3/4 - 2/4 Now you can subtract 2/4 from from 3/4: 3/4 - 2/4 = 1/4 t = 1/4 There are the solutions and explanations to all your questions, if you need any more help, please don't hesitate to ask me.  Have a great day and happy problem solving :D
Read More: ...

Solve for 2x+1=-15-2x

Solve for 2x+1=-15-2x I am really confused with how to solve this problem, please help! What you need to do is get all the x terms on the left side of the equation, and all the constants on the right side. Remember that as long as we perform the same operation on both sides of the equation, we still have an equation, i.e., both sides remain equal, even though the value has changed. 2x + 1 = -15 - 2x On the right side, 2x is being subtracted. Add 2x to both sides of the equation. 2x + 1 + 2x = -15 - 2x + 2x On the right side, the 2x terms cancel out. On the left side, go ahead and add the x terms. 2x + 1 + 2x = -15 4x + 1 = -15 We want to remove the constant (1) from the left side, so subtract 1 from both sides. 4x + 1 - 1 = -15 - 1 Perform the operations. 4x = -16 The final step is to divide both sides by 4. 4x / 4 = -16 / 4 x = -4
Read More: ...

This is a logarithm problem that I need help to solve this problem and if possible a step by step answer here is the problem log4(x-3)^3=4

Log to base 4 of (x-3)^3 or log to base 10 of 4(x-3)^3 or natural log of 4(x-3)^3? I'll answer all three. Log to base 4 of (x-3)^3=4 The log of the cube of a quantity is 3 times the log of the quantity, so 3log(x-3)=4 and log(x-3)=4/3. To solve this raise both sides as powers of 4: x-3=4^4/3, so x=3+4^4/3=3+6.35=9.35. To find 4^4/3 I took 4(ln4)/3=1.8484 and then calculated e^1.8484=6.35. I could also have calculated using log to base 10 instead of e. Log to base 10 of 4(x-3)^3=4 Log4(x-3)^3=log4+3log(x-3)=4. So 3log(x-3)=4-log4=3.39794 and log(x-3)=3.39794/3=1.13265. This time we raise both sides as powers of 10: (x-3)=10^1.13265=13.572, so x=16.572. Natural log of 4(x-3)^3=4 Ln4(x-3)^3=ln4+3ln(x-3)=4. So 3ln(x-3)=4-ln4=2.6137 and log(x-3)=2.6137/3=0.8712. Raise both sides as powers of e: (x-3)=e^0.8712=2.3899, so x=5.3899.
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || || Terms of Use || Contact || Privacy Policy
Load time: 0.1648 seconds